Disrupted attentional learning in high schizotypy: Evidence of aberrant salience. (31st December 2015) - Haselgrove, Mark; Le Pelley, Mike E.; Singh, Navreen K.; Teow, Hui Qi; Morris, Richard W.; Green, Melissa J.; Griffiths, Oren; Killcross, Simon
Abstract : The relationship between learned variations in attention and schizotypy was examined in two experiments. In Experiment 1, participants low on a negative subscale of schizotypy exhibited an explicit bias in overt attention towards stimuli that were established as predictive of a trial outcome, relative to stimuli that were irrelevant. The same participants also showed a bias in learning about these stimuli when they presented in a novel context. Neither of these effects was observed in participants high in schizotypy. In Experiment 2, participants low on the negative subscale of schizotypy exhibited faster reaction times towards a target that was cued by a stimulus that had a history of predictive validity relative to a stimulus that had a history of irrelevance. Again, this effect was not present in participants high in schizotypy. These results imply a disruption in the normal allocation of attention to cues that have predictive significance in schizotypy.